Review of the existing maximum residue levels for flubendiamide according to Article 12 of Regulation (EC) No 396/2005 - Anastassiadou, Maria (EFSA J, 2020)
According to Article 12 of Regulation (EC) No 396/2005, EFSA has reviewed the maximum residue levels (MRLs) currently established at European level for the pesticide active substance flubendiamide. To assess the occurrence of flubendiamide residues in plants, processed commodities, rotational crops and livestock, EFSA considered the conclusions derived in the framework of Commission Regulation (EU) No 188/2011, the MRLs established by the Codex Alimentarius Commission as well as the import tolerances (including the supporting residues data). No European authorisation was reported by Member States. Based on the assessment of the available data, MRL proposals were derived and a consumer risk assessment was carried out. Some information required by the regulatory framework was missing and a possible acute risk to consumers was identified. Hence, the consumer risk assessment is considered indicative only, some MRL proposals derived by EFSA still requires further consideration by risk managers and measures for reduction of the consumer exposure should also be considered.